H-MXene composite material as well as preparation method and application thereof

By using the H-MXNENE composite material of hydrogen bonds as the anode material of zinc ion battery, the problem of the growth, corrosion, hydrogen analysis, and cycle stability of the battery can be solved, and the mechanical stability and cycle stability of the battery are improved , With the excellent performance of super long life and low overvoltage.

CN119381454APending Publication Date: 2025-01-28CHAOWEI POWER GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310915561.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing aqueous zinc ion batteries are prone to problems such as dendrites growth, corrosion, hydrogen evolution and poor circulation stability.

Method used

The H-MXENE composite material is used as an anode material, and the MXENE and polyethylene amine are prepared into PEI-MXENE hydrogel through gel method. The subject is to improve the mechanical stability and cycle performance of the battery.

Benefits of technology

The mechanical stability and cycle stability of zinc ion batteries are realized. It has an ultra -high area/rate capacity and excellent cycle life. It can maintain long life and low voltage at ultra -high current density and surface capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381454A_ABST
    Figure CN119381454A_ABST
Patent Text Reader

Abstract

The invention discloses an h-MXene composite material as well as a preparation method and application thereof, belongs to the technical field of aqueous zinc ion batteries, and solves the problems of easiness in dendritic crystal growth, serious corrosion, hydrogen evolution and poor cycling stability of an anode of a current aqueous zinc ion battery. The h-MXene composite material is prepared from the following raw materials: MXene and polyethyleneimine, wherein the MXene is Ti < 3 > C < 2 > T < x >. The preparation method of the h-MXene composite material comprises the following steps: firstly, preparing PEI-MXene hydrogel from a polyethyleneimine solution and an MXene solution through a gel method, and then freeze-drying and aging to obtain the hydrogen bond cross-linked MXene composite material. The h-MXene composite material disclosed by the invention is good in mechanical stability, and the Zn (at) h-MXene anode material prepared from the h-MXene composite material has excellent cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of zinc ion batteries, and in particular relates to an h-MXene composite material and a preparation method and application thereof. Background Art

[0002] Zinc metal batteries (ZMBs) are promising candidates for their low electrochemical potential (-0.76 V vs standard hydrogen electrode), high volumetric capacity (5855 mAh cm -3 ), abundant reserves and high-safety aqueous electrolytes are considered to be a promising candidate battery. However, the two fundamental dilemmas of high chemical reactivity and infinite relative volume change of Zn metal anode during cycling limit the practical application of Zn metal batteries. It should be pointed out that the drastic volume change during cycling will lead to the generation of "dead zinc" and repeated accumulation / decomposition of the naturally grown solid electrolyte interface (SEI), resulting in irreversible zinc consumption and interface reconstruction. In addition, due to the high chemical reactivity of zinc metal at the broken SEI film, an inhomogeneous and ion-hindered new SEI will spontaneously form, which will lead to Zn 2+ flux non-uniformity and increased dendrite growth at the anode interface, which are exacerbated with fast / deep galvanizing / stripping at high current density and high capacity.

[0003] Currently, methods such as optimizing electrolyte composition and concentration, designing functional protective layers, modifying separators, and constructing three-dimensional (3D) host structures have been proposed to overcome these problems from different perspectives. Among the reported strategies, Zn composite anodes can be constructed by implanting Zn metal in conductive or chemically zinc-philic 3D scaffolds. Porous scaffolds with large surface area and high conductivity can reduce local current density and enable Zn 2+ The ion flux is homogenized, thereby suppressing the growth of Zn dendrites. In addition, super-Zn-philic porous scaffolds can reduce the nucleation overpotential of Zn and induce Zn nucleation within the framework to accommodate the volume change during the electroplating / stripping process. To this end, 3D porous and conductive scaffolds have been proposed. However, huge internal stress fluctuations may inevitably damage these scaffolds due to their poor mechanical toughness during repeated Zn plating / stripping cycles, especially at high current density or capacity, which also leads to reduced energy density and limited cycle life of ZMBs. Therefore, advanced scaffolds must be prepared as Zn hosts, which simultaneously have excellent mechanical stability, strong Zn-philicity and high conductivity to improve the electrochemical performance of ZMBs at high current density and areal capacity. Summary of the invention

[0004] In view of the above analysis, the present invention aims to provide an h-MXene composite material and a preparation method and application thereof, so as to solve one of the following technical problems: the existing aqueous zinc ion batteries are prone to dendrite growth, corrosion, hydrogen evolution and poor cycle stability.

[0005] The purpose of the present invention is mainly achieved through the following technical solutions:

[0006] The present invention provides an h-MXene composite material. The raw materials for preparing the h-MXene composite material include MXene and polyethyleneimine. The MXene is Ti3C2T x .

[0007] Furthermore, the mass ratio of MXene to polyethyleneimine is 3:(300-1000).

[0008] Furthermore, the thickness of the h-MXene composite material is 410 to 450 μm.

[0009] Furthermore, the h-MXene composite material has a hierarchical porous structure with an average pore size of 8 to 13 μm and a pore wall thickness of 80 to 130 nm.

[0010] Furthermore, the average channel spacing of the pore walls of the h-MXene composite material is 1.2 to 1.4 nm.

[0011] The present invention also provides a method for preparing the above-mentioned h-MXene composite material. The preparation method first prepares a polyethyleneimine solution and a MXene solution into a PEI-MXene hydrogel by a gel method, and then obtains a hydrogen-bonded cross-linked MXene composite material, i.e., an h-MXene composite material, by freeze-drying and aging.

[0012] Furthermore, the preparation method comprises the following steps:

[0013] Step 1, ultrasonically dispersing MXene powder in distilled water to prepare a MXene dispersion;

[0014] Step 2, adding the PEI solution to the MXene dispersion, stirring to obtain a mixture, vacuum filtering the mixture using a filter membrane, and washing it with distilled water several times to obtain a PEI-MXene hydrogel;

[0015] Step 3, adding the collected PEI-MXene hydrogel to distilled water and vigorously stirring it using a vortex mixer to obtain a uniform PEI-MXene viscous hydrogel;

[0016] Step 4: directly scrape the PEI-MXene viscous hydrogel onto the substrate, and then immediately immerse it in liquid nitrogen for ice-templating to obtain PEI-MXene foam;

[0017] Step 5: freeze-dry the PEI-MXene foam; then, age the PEI-MXene foam at room temperature to prepare an h-MXene composite material.

[0018] Furthermore, in step 2, the concentration of the PEI solution is (0.7-0.9) wt%.

[0019] Furthermore, in step 5, the freeze-drying time is 22 to 26 hours.

[0020] The present invention also provides an application of an h-MXene composite material, wherein the h-MXene composite material is used in an aqueous zinc ion battery.

[0021] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0022] a) The formation of hydrogen bonds in the h-MXene composite material of the present invention makes the h-MXene composite material have good mechanical stability, and the Young's modulus of the h-MXene composite material is greater than 700 kPa, for example, 714 to 1477 kPa.

[0023] b) The materials required in the preparation process of the h-MXene composite material of the present invention are readily available and abundant in reserves, and have high electrical conductivity.

[0024] c) The preparation method of the h-MXene composite material of the present invention is simple, does not require complex equipment, has low raw material prices, introduces few impurities, has a short whole chain time, and is suitable for large-scale industrial production.

[0025] d) Zn@h-MXene synthesized from the h-MXene composite material of the present invention as an anode material breaks the problems of poor mechanical stability and poor cycle stability of traditional anodes, and uses a hydrogen-bonded cross-linked MXene skeleton (i.e., h-MXene) as the Zn main body to obtain a stable Zn composite anode with ultra-high area / rate capacity and excellent cycle life. The formation of hydrogen bonds in the skeleton gives Zn@h-MXene good mechanical properties, which can buffer huge internal stress fluctuations and avoid electrode collapse or disintegration during rapid depth galvanizing and stripping processes. In addition, the zinc-affinity cross-linked MXene nanosheets with high conductivity can uniformly induce Zn deposition without dendrites. The anode material of the present invention shows ultra-long life and excellent cycle stability at ultra-high current density and surface capacity.

[0026] e) The aqueous zinc ion battery of the present invention has excellent performance, stable cycle performance and low overvoltage.

[0027] Other features and advantages of the present invention will be described in the following description, and part of them will become obvious from the description, or will be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the written description. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are only for the purpose of illustrating the particular invention and are not to be considered as limiting the invention. The same reference symbols denote the same components throughout the accompanying drawings.

[0029] Figure 1 These are SEM and TEM images of the h1-MXene composite material of Example 1 of the present invention;

[0030] Figure 2 It is Fourier transform infrared spectrometer and X-ray photoelectron spectrometer;

[0031] Figure 3 are X-ray diffraction patterns, nitrogen adsorption-desorption isotherms and pore size distribution curves;

[0032] Figure 4 This is a characterization image of the electrode during zinc deposition using in-situ optical microscopy;

[0033] Figure 5 This is the electrochemical test result diagram;

[0034] Figure 6 This is a characterization diagram of the structural stability of the electrode during the galvanizing / stripping process simulated by COMSOL;

[0035] Figure 7 The electrode is characterized using DFT calculations, atomic force microscopy, and Kelvin probe force microscopy. DETAILED DESCRIPTION

[0036] The following is a further detailed description of an h-MXene composite material, a preparation method and an application thereof in conjunction with specific examples. These examples are only for comparison and explanation purposes, and the present invention is not limited to these examples.

[0037] The present invention provides an h-MXene composite material. The raw materials for preparing the h-MXene composite material include MXene and polyethyleneimine. The MXene is Ti3C2T x .

[0038] Specifically, considering that too high a mass of polyethyleneimine will increase the cost and affect the mechanical properties, and too low a mass of polyethyleneimine will not form an effective hydrogen bond network, the mass ratio of the above MXene to polyethyleneimine is controlled to be 3: (300-1000).

[0039] Specifically, if the thickness of the h-MXene composite material is too large, the thickness of the electrode will increase and reduce its electrochemical performance, and if it is too small, it will be easy to break. Therefore, the thickness of the h-MXene composite material is controlled to be 410-450 μm.

[0040] Specifically, the h-MXene composite material has a hierarchical porous structure. Considering that an average pore size that is too large or too small is not conducive to the deposition of zinc metal. Therefore, the average pore size is controlled to be 8 to 13 μm. When the h-MXene composite material is used as an anode material, the hierarchical porous structure of the h-MXene composite material is conducive to confining the deposited zinc in a hierarchical porous scaffold.

[0041] Specifically, the pore wall of the h-MXene composite material is polyamine. Too large or too small a thickness of the pore wall will affect the mechanical properties of the electrode. Therefore, the thickness of the pore wall is controlled to be 80 to 130 nm.

[0042] Specifically, the average channel spacing of the pore walls of the h-MXene composite material is 1.2 to 1.4 nm.

[0043] Specifically, the h-MXene composite material has no wrinkles or cracks around the pore wall joints, and the components have good dispersion.

[0044] Specifically, the electrical conductivity of the h-MXene composite material is about 150 to 430 S m -1 The specific surface area of ​​h-MXene composite materials is about 20 to 30 m 2 g -1 .

[0045] Specifically, the h-MXene composite material has excellent mechanical properties. The Young's modulus of the h-MXene composite material is above 700 kPa, for example, 714 to 1477 kPa, which is significantly higher than 471 kPa of the pure MXene skeleton.

[0046] The present invention provides a method for preparing an h-MXene composite material. The preparation method first prepares a polyethyleneimine (PEI for short) solution and a MXene solution into a PEI-MXene hydrogel by a gel method, and then obtains a hydrogen-bonded cross-linked MXene composite material, i.e., an h-MXene composite material, by freeze-drying and aging.

[0047] Specifically, the preparation method comprises the following steps:

[0048] Step 1, ultrasonically dispersing MXene powder in distilled water to prepare a MXene dispersion;

[0049] Step 2, adding the PEI solution to the MXene dispersion, stirring to obtain a mixture, vacuum filtering the mixture using a filter membrane, and washing it with distilled water several times to obtain a PEI-MXene hydrogel;

[0050] Step 3, adding the collected PEI-MXene hydrogel to distilled water and vigorously stirring it using a vortex mixer to obtain a uniform PEI-MXene viscous hydrogel;

[0051] Step 4: directly scrape the PEI-MXene viscous hydrogel onto the substrate, and then immediately immerse it in liquid nitrogen for ice-templating to obtain PEI-MXene foam;

[0052] Step 5: freeze-dry the PEI-MXene foam; then, age the PEI-MXene foam at room temperature to prepare an h-MXene composite material.

[0053] Specifically, in the above step 1, if the concentration of the MXene dispersion is too high, it will increase the cost, and if it is too low, it will reduce the conductivity of the electrode. Therefore, the concentration of the MXene dispersion is controlled to be (4-6) mg·mL -1 .

[0054] Specifically, in the above step 1, if the dispersion time is too long, the efficiency will be reduced, and if it is too short, it will lead to uneven mixing. Therefore, the dispersion time is controlled to be 0.4 to 0.6 hours.

[0055] Specifically, in the above step 2, if the concentration of the PEI solution is too high, the cost will increase and the mechanical properties will be affected, and if it is too low, an effective hydrogen bond network will not be formed. Therefore, the concentration of the PEI solution is controlled to be (0.7-0.9) wt%.

[0056] Specifically, in the above step 2, the mass ratio of MXene to polyethyleneimine is controlled to be 3:(300-1000).

[0057] Specifically, in the above step 2, if the stirring time is too long, the cost will increase, and if it is too short, the mixing will be uneven. Therefore, the stirring speed is controlled to be 780-820 rpm, and the stirring time is 15-25 minutes.

[0058] Specifically, in the above step 2, if the pore size of the filter membrane is too large or too small, it will have an impact. Therefore, the pore size of the filter membrane is controlled to be 0.4-0.5 μm.

[0059] Specifically, in the above step 3, if the speed of the vortex mixer is too high, the material will be damaged, and if it is too low, the material will not be stirred. If the stirring time is too long, the cost will increase, and if it is too short, the mixing will be uneven. Therefore, the speed of the vortex mixer is controlled to be 980-1020 rpm, and the stirring time is 25-35 min.

[0060] Specifically, in the above step 5, if the freeze drying time is too short, the freeze drying effect will not be achieved, and if it is too long, the production cost will increase. Therefore, the freeze drying time is controlled to be 22 to 26 hours.

[0061] Specifically, in the above step 5, if the aging time is too short, the molding will not occur, and if it is too long, the efficiency will be reduced. Therefore, the aging time is controlled to be 1 to 2 hours.

[0062] The present invention also provides an application of the h-MXene composite material, wherein the h-MXene composite material is used as an anode of an aqueous zinc ion battery.

[0063] The present invention also provides an aqueous zinc ion battery anode material (abbreviated as Zn@h-MXene), and the raw materials of the aqueous zinc ion battery anode material include Zn and the above-mentioned h-MXene composite material.

[0064] The present invention also provides a method for preparing an aqueous zinc ion battery anode material, comprising:

[0065] Zn@h-MXene was obtained by electrodeposition of Zn on the hierarchically porous h-MXene skeleton.

[0066] Specifically, in the above preparation method, when the deposition capacity is small, the skeleton utilization rate is reduced, which will reduce the electrochemical performance of the battery; when the deposition capacity is large, Zn will be deposited unevenly on the skeleton, which will also affect the battery performance; therefore, at 1 mA cm -2 At a current density of about 100 Å, ZnSO4 was used as the electrolyte to electro-deposit Zn on the hierarchical porous h-MXene skeleton, where the deposition capacity of Zn was controlled to be 1-10 mAh cm -2 within the range.

[0067] It should be noted that when zinc is deposited on the h-MXene skeleton, the metal Zn is uniformly deposited on the pore wall due to the Ti3C2T x It is a highly zinc-philic substance with high binding energy to Zn atoms. In addition, the -F groups on the surface of MXene can bind Zn 2+ The generation of ZnF2 can significantly reduce the desolvation activity energy and effectively redistribute Zn 2+ ion flux, leading to facile and stable Zn deposition kinetics. Therefore, MXene nanosheets can significantly reduce the Zn deposition overpotential, thereby guiding the uniform deposition of Zn throughout the h-MXene framework.

[0068] The present invention also provides an aqueous zinc ion battery, which uses the aqueous zinc ion battery anode material as an anode.

[0069] Compared with the prior art, the formation of hydrogen bonds in the h-MXene composite material of the present invention makes the h-MXene composite material have good mechanical stability, and the Young's modulus of the h-MXene composite material is above 700 kPa, for example, 714 to 1477 kPa.

[0070] The materials required in the preparation process of the h-MXene composite material of the present invention are readily available and abundant in reserves, and have high electrical conductivity.

[0071] The preparation method of the h-MXene composite material of the present invention is simple, does not require complex equipment, has low raw material prices, introduces less impurities, has a short whole chain time, and is suitable for large-scale industrial production.

[0072] The Zn@h-MXene synthesized from the h-MXene composite material of the present invention as an anode material breaks the problems of poor mechanical stability and poor cycle stability of the traditional anode, and uses a hydrogen-bonded cross-linked MXene skeleton (i.e., h-MXene) as the Zn main body to obtain a stable Zn composite anode, while having ultra-high area / rate capacity and excellent cycle life. The formation of hydrogen bonds in the skeleton gives Zn@h-MXene good mechanical properties, which can buffer huge internal stress fluctuations and avoid electrode collapse or disintegration in the fast-depth zinc plating and stripping process. In addition, the zinc-affinity cross-linked MXene nanosheets with high conductivity can uniformly induce Zn deposition without dendrites. The anode material of the present invention shows ultra-long life and excellent cycle stability at ultra-high current density and surface capacity.

[0073] The aqueous zinc ion battery of the present invention has excellent performance, stable cycle performance and low overvoltage.

[0074] Example 1

[0075] This embodiment provides an h-MXene composite material, and a method for preparing the h-MXene composite material, comprising:

[0076] Step 1, ultrasonically dispersing MXene powder in distilled water to prepare a MXene dispersion;

[0077] Step 2: Add the PEI solution to the MXene dispersion, stir vigorously to obtain a mixture, vacuum filter the mixture using a filter membrane, and rinse with distilled water several times to obtain a PEI-MXene hydrogel;

[0078] Step 3, adding the collected PEI-MXene hydrogel to distilled water and vigorously stirring it using a vortex mixer to obtain a uniform PEI-MXene viscous hydrogel;

[0079] Step 4: directly scrape the PEI-MXene viscous hydrogel onto the substrate, and then immediately immerse it in liquid nitrogen for ice-templating to obtain PEI-MXene foam;

[0080] Step 5: freeze-dry the PEI-MXene foam; then, age the PEI-MXene foam at room temperature to prepare the h1-MXene composite material.

[0081] Specifically, in step 1 above, the concentration of the MXene dispersion is 5 mg mL -1 , the dispersion time is 0.5h.

[0082] Specifically, in the above step 2, the concentration of the PEI solution is 0.8 wt %.

[0083] Specifically, in the above step 2, the mass ratio of MXene to polyethyleneimine is controlled to be 3:500.

[0084] Specifically, in the above step 2, the stirring speed is controlled to 800 rpm and the stirring is performed for 20 minutes.

[0085] Specifically, in the above step 2, the pore size of the filter membrane is controlled to be 0.45 μm.

[0086] Specifically, in the above step 3, the rotation speed of the vortex mixer is controlled to be 1000 rpm and the stirring time is 30 min.

[0087] Specifically, in the above step 5, the freeze-drying temperature is controlled to be 0° C. and the time is controlled to be 24 hours.

[0088] Specifically, in the above step 5, the aging time is controlled to be 1 hour.

[0089] In this embodiment, the thickness of the h1-MXene composite material is about 430 μm, the average pore size is about 10 μm, the pore wall of the h1-MXene composite material is a polyamine with a thickness of about 100 nm, the average channel spacing of the pore wall is 1.32 nm, and no wrinkles or cracks appear around the pore wall joints; the conductivity of the h1-MXene composite material is about 300 S m -1 The specific surface area of ​​h1-MXene is about 26.23 m 2 g -1 ; The h1-MXene composite material has excellent mechanical properties, with a Young's modulus of 1224kPa.

[0090] Example 2

[0091] This embodiment provides an h-MXene composite material. The preparation method of the h-MXene composite material in this embodiment is substantially the same as that in Embodiment 1, except that:

[0092] In step 2, the mass ratio of MXene and polyethyleneimine was controlled to be 3:1000.

[0093] In step 2, the stirring speed was controlled to 810 rpm and the stirring was performed for 18 min.

[0094] In step 2, the pore size of the filter membrane is controlled to be 0.43 μm.

[0095] In step 3, the rotation speed of the vortex mixer is controlled to be 1010 rpm and the stirring time is 30 min.

[0096] Specifically, in the above step 5, the freeze-drying temperature is controlled to be 0° C. and the time is controlled to be 25 h.

[0097] In step 5, h 1.5 -MXene composites.

[0098] In this embodiment, h 1.5 -MXene composite material thickness is about 435μm, the average pore size is about 9μm, h 1.5 The pore wall of the -MXene composite material is a polyamine with a thickness of about 130nm, and the average channel spacing of the pore wall is 1.21nm; 1.5 -The electrical conductivity of MXene composites is about 150 S m -1 ,h 1.5 -MXene has a specific surface area of ​​about 24.5 m 2 g -1 .h 1.5 -MXene composites have excellent mechanical properties, with a Young's modulus of 1477 kPa.

[0099] Example 3

[0100] This embodiment provides an h-MXene composite material. The preparation method of the h-MXene composite material in this embodiment is substantially the same as that in Embodiment 1, except that:

[0101] In step 2, the mass ratio of MXene and polyethyleneimine was controlled to be 9:1000.

[0102] In step 2, the stirring speed was controlled to 790 rpm and the stirring was carried out for 25 min.

[0103] In step 2, the pore size of the filter membrane is controlled to be 0.46 μm.

[0104] In step 3, the rotation speed of the vortex mixer was controlled to be 990 rpm and the stirring time was 33 min.

[0105] Specifically, in the above step 5, the freeze-drying temperature is controlled to be 0° C. and the time is controlled to be 25 h.

[0106] In step 5, h 0.5 -MXene composites.

[0107] In this embodiment, h 0.5 The thickness of the MXene composite material is about 425 μm, the average pore size is about 11 μm, and the h 0.5 The pore wall of the MXene composite material is a polyamine with a thickness of about 80nm, the average channel spacing of the pore wall is 1.4nm, and there are no wrinkles and cracks around the pore wall joints; 0.5 -The electrical conductivity of MXene composites is about 420 S m -1 ,h 0.5 -MXene has a specific surface area of ​​about 27.1 m 2 g -1 .H 0.5 -MXene composites have excellent mechanical properties, with a Young's modulus of 714 kPa.

[0108] Example 4

[0109] This embodiment provides an aqueous zinc ion battery anode (abbreviated as Zn@h-MXene), and the raw materials of Zn@h-MXene include Zn and the above-mentioned h1-MXene composite material.

[0110] The preparation method of Zn@h-MXene comprises:

[0111] At 1mA cm -2 At a current density of 1.5 200 mAh cm, Zn was electrodeposited on the hierarchically porous h1-MXene skeleton using ZnSO4 as the electrolyte, and the deposition capacity of Zn was controlled to be 1-10 mAh cm -2 within the range.

[0112] The aqueous zinc ion battery anode of this embodiment shows ultra-long life and excellent cycle stability at ultra-high current density and surface capacity. For example, the electrodeposition of 10 mAh cm -2 When Zn is present at ultra-high current density (1000mA g -1 ), after 2000 cycles, the high capacity is maintained at 184.4 mAh g -1 , stable Coulombic efficiency up to 99.6%; electrodeposition 1mAh cm -2 When the current density is fixed at 20 mA cm -2 The symmetric battery based on Zn@h1-MXene electrode provides 1000 stable cycle performances with a stable Coulombic efficiency of more than 99.5%; the electrodeposition of 5 mAh cm -2 When the current density is fixed at 20 mA cm -2 The symmetric battery based on Zn@h1-MXene electrode provides 250 stable cycling performances with a stable Coulombic efficiency of over 99%.

[0113] Example 5

[0114] This embodiment provides an aqueous zinc ion battery anode (abbreviated as Zn@h-MXene). The raw materials of Zn@h-MXene include Zn and the above-mentioned h 0.5 -MXene composites.

[0115] The preparation method of Zn@h-MXene was the same as that in Example 4, and 10 mAh cm -2 of metal Zn.

[0116] The anode of the aqueous zinc ion battery of this embodiment has a small amount of hydrogen bond cross-linking and high conductivity. -2 Under the current density, the continuous plating / stripping cycle time is about 10 hours. This may be because its weak mechanical properties make it difficult to overcome the stress fluctuations during the plating / stripping process, causing structural collapse and thus affecting electronic conduction.

[0117] Example 6

[0118] This embodiment provides an aqueous zinc ion battery anode (abbreviated as Zn@h-MXene). The raw materials of Zn@h-MXene include Zn and the above-mentioned h 1.5 -MXene composites.

[0119] The preparation method of Zn@h-MXene was the same as that in Example 4, and 10 mAh cm -2 of metal Zn.

[0120] The aqueous zinc ion battery anode of this embodiment has excessive hydrogen bonding and low conductivity. -2 The plating / stripping cycle can be continued for 25h at the current density. Zn@h 1.5 -MXene anodes show higher overpotential and shorter cycle life than Zn@h1-MXene anodes, which may be due to the low conductivity and excessive PEI reducing the nucleation inducing ability of the framework.

[0121] Example 7

[0122] This embodiment provides an aqueous zinc ion battery, using the Zn@h1-MXene of the above embodiment 4 as the anode.

[0123] The aqueous zinc ion battery of this embodiment has excellent performance when the current density is fixed at 20 mA cm -2 , with an area capacity of 1 mAh cm -2 When quenched, the symmetric cells based on Zn@h1-MXene electrodes provide stable cycling performance with a low overvoltage (~68 mV) up to 6000 cycles.

[0124] Comparative Example 1

[0125] This comparative example provides a performance comparison test of a bare Zn||MnO2 full cell, whose capacity shows a significant decrease in the first 50 cycles and only decays to less than 31.8 mAh g after 2000 cycles. –1 The Zn@h1-MXene||MnO2 full battery has a high current density (1000mA g -1 ), after 2000 cycles, the high capacity is maintained at 184.4 mAh g -1 , with a stable Coulombic efficiency of up to 99.6%. The hierarchical porous structure of the h-MXene skeleton can induce the plating and stripping of the zinc composite anode and inhibit the growth of dendrites, proving to be of great significance in improving the reversibility of the zinc anode and the cycling performance of the entire battery.

[0126] Figure 1 Shown are scanning electron microscope (SEM) images and transmission electron microscope (TEM) images of the h1-MXene composite material of Example 1, Figure 1 In the figure, (a)-(d) are SEM images at different magnifications, (e) is the TEM image of the h1-MXene composite material, and (f) is the TEM image of MXene. From (a)-(c), it can be seen that there is a hierarchical structure of PEI cross-linked continuous MXene assembly in the h1-MXene composite material. The thickness of the h1-MXene composite material is about 430μm, the average pore size is about 10μm, and the pore wall of the h1-MXene composite material is a polyamine with a thickness of about 100nm; from (c), it can be seen that there are no wrinkles and cracks around the pore wall joints, which proves the structural integrity of this hydrogen bond cross-linked skeleton.

[0127] To demonstrate the dispersion of the components, energy dispersive X-ray (EDX) spectroscopy was performed to confirm the elemental mapping within h1-MXene. Figure 1 As can be seen in (d), C, Ti, F, and N are uniformly distributed in the h1-MXene scaffold. Figure 1 It can be seen from (e) and (f) that the average channel spacing of the pore walls in h1-MXene is about 1.32 nm, which is larger than the average channel spacing of MXene about 1.16 nm, indicating that with the introduction of PEI, the spacing between MXene nanosheets becomes wider.

[0128] Figure 2 , Figure 3 Shown is the characterization of the synthesized h1-MXene composite material using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and nitrogen adsorption desorption (BET) physical characterization:

[0129] Figure 2 (a) is the Fourier transform infrared spectrum, which is used to confirm the interaction between MXene and PEI in h1-MXene. 1305 and 1045 cm -1 The two absorption peaks at 3434 cm-1 can be attributed to CN stretching and deformation. Due to the presence of PEI after the addition of the crosslinker, the absorption peak of the hydroxyl group in MXene increases from 3434 cm-1 to 3434 cm-1. -1 Move to 3429cm -1 The above results indicate that the hydrogen bonding interaction of PEI mainly leads to the cross-linking between MXene nanosheets and PEI. We performed X-ray photoelectron spectroscopy (XPS) measurements to investigate the bond formation of MXene and PEI.

[0130] Figure 2 In (b)-(d) are X-ray photoelectron spectroscopy (XPS) images, and (b)-(d) show high-resolution XPS spectra of N1s, Ti 2p, and C1s. As shown in (b), the N 1s XPS spectrum shows three peaks at 398.8 eV, 399.5 eV, and 401.1 eV, respectively, which are attributed to primary amine, secondary amine, and tertiary amine, which further proves the composition of MXene and PEI; as shown in (c), in the Ti2p XPS spectrum, the peaks at 454.7 and 460.8 eV correspond to Ti-C bonds, and the peaks at 455.4 and 461.8 eV correspond to Ti 2+ , the peaks at 456.9 and 462.7 eV correspond to Ti 3+ , the fact that the peaks of Ti-O bonds are located at 458.4 eV and 463.7 eV, and the peak of Ti-F is located at 459.7 eV is basically consistent with that of pure MXene.

[0131] Figure 3 In the figure, (a) is the XRD pattern of MXene and h1-Mxene, which further confirms the change in the spacing of MXene nanosheets after adding the crosslinker. Before adding the crosslinker, the diffraction peak of (001) is 2θ=7.6°. After adding PEI, the diffraction peak of (001) moves to the left to 2θ=6.7°, indicating that the spacing of the MXene layer is expanded after adding the crosslinker. Figure 3 In the figure, (b) is pure MXene, h 0.5 -MXene, h1-MXene and h 1.5 It can be seen that even though the conductivity of h-MXene decreases with the increase of the insulating PEI mass ratio, h1-MXene still maintains a high conductivity of 300 S m -1 conductivity, thereby ensuring that charges propagate at a higher rate throughout the composite material. Figure 3In (c), the nitrogen adsorption-desorption isotherm of h1-Mxene composite material is shown. Figure 3 (d) is the pore size distribution curve of h1-Mxene. It can be seen that the h1-Mxene composite material has a pore size of about 26.23 m 2 g -1 The high specific surface area provides a large contact area for zinc deposition.

[0132] Figure 4 Shown is the characterization of the electrode during zinc deposition using in-situ optical microscopy:

[0133] Figure 4 In the figure, (a) shows the morphology of the zinc foil electrode after different electroplating times: the initial zinc foil electrode presents a glazed edge. After 10 minutes of electrochemical plating, protrusions can be clearly observed on the edge of the zinc foil electrode, indicating uneven zinc plating. As the electroplating time increases, these heterogeneous protrusions gradually evolve into dendrites on the bare zinc electrode.

[0134] Figure 4 (b) shows the morphology of h1-MXene electrodes after different electroplating times: the h1-MXene electrode exhibits a uniform zinc plating process, and there are no obvious protrusions or dendrites on the h1-MXene electrode even after 60 minutes of electrochemical plating. (c1)-(c3) show 1mAh cm -2 SEM images at different magnifications, (d1)-(d3) show 5 mAh cm -2 SEM images at different magnifications, (e1)-(e3) show 10 mAh cm -2 The SEM images at different magnifications are shown below. It can be seen that in the Zn@h1-MXene composite electrode, the h1-MXene scaffold has excellent mechanical properties and excellent zinc deposition nucleation induction. x It is a highly zinc-philic substance with high binding energy to Zn atoms. In addition, the -F groups on the surface of MXene can bind Zn 2+ The generation of ZnF2 can significantly reduce the desolvation activity energy and effectively redistribute Zn 2+ ion flux, leading to facile and stable Zn deposition kinetics. Therefore, MXene nanosheets can significantly reduce the nucleation overpotential of Zn, thereby guiding the uniform deposition of Zn throughout the h1-MXene framework.

[0135] The present invention conducts electrochemical tests on the prepared Zn@h1-MXene:

[0136] like Figure 5 Comparison of the cycling performance of Zn@pure MXene and Zn@h1-MXene composite anode symmetric cells at current densities of: (a) 20 mA cm-2 and (b) 40 mA cm -2 , with a fixed capacity of 1 mAh cm -2 (c) Zn@h1-MXene composite anode at 1 to 40 mA cm -2 Time-voltage curves at different current densities. (d) Comparison of the cycle life of symmetrical cells of Zn@h1-MXene composite anode and previously reported 3DZn composite anode at different current densities. (e) CV curves of Zn@h1-MXene / / MnO2 battery and Zn / / MnO2 battery measured from 0.8 to 1.8V. (f) Comparison of the 5th cycle CV curves of Zn / / MnO2 and Zn@h1-MXene / / MnO2 batteries. (g) Comparison of the 5th cycle CV curves of Zn / / MnO2 and Zn@h1-MXene / / MnO2 batteries at a current density of 1000mA g -1 (a) It can be seen that when the current density is fixed at 20 mA cm -2 , with an area capacity of 1 mAh cm -2 When the current density is reduced to 40 mA cm, the symmetric battery based on Zn@h1-MXene electrode provides stable cycling performance with up to 6000 stable cycles at a low overvoltage (68 mV). (b) It can be seen that -2 , Zn@h1-MXene battery maintained remarkable cycle stability for more than 5000 cycles, while Zn@Pure-MXene without additional hydrogen bond crosslinking lasted no more than 10 hours. Zn@Pure-MXene anode has higher overpotential and shorter cycle life than Zn@h1-MXene composite anode. The possible reason is that its weak mechanical properties make it difficult to overcome the structural collapse caused by stress fluctuations during plating / stripping, which in turn affects electronic conduction. Zn@h1-MXene composite anodes were compared and evaluated by testing symmetric cells at different current densities. Figure 5 As shown in (c), the low voltage hysteresis at ultra-high current density indicates that Zn 2+ The fast transport kinetics and excellent interfacial stability of the nanostructured carbon nanotubes are consistent with the above results, indicating a clear advantage over Zn foil. Figure 5 As shown in (d), the cycle life of the Zn@h1-MXene electrode is compared with that of the previously reported Zn metal anode in a symmetric cell. -2 At an ultra-high current density of 1.3 Å, the Zn@h1-MXene composite anode of the present invention surpasses almost all other previously reported zinc metal anodes.

[0137] In order to evaluate the performance of the full battery, MnO2 was used as the cathode, Zn@h1-MXene was used as the anode, and the electrolyte was a mixed solution of 1MZnSO4 and 0.1M MnSO4 to form a full battery. The test results are shown in Figure 5 As shown in Figure e, compared with the pure zinc battery, especially in the first five cycles, it is obvious that the Zn@h1-MXene||MnO2 battery shows almost overlapping curves in different cycles, which means that it has good reversibility due to the h1-MXene protection mechanism. Voltage hysteresis is an important evidence for judging the reversibility of the battery. Figure 5 Compared with the bare zinc foil battery, the Zn@h1-MXene||MnO2 shown in (f) has higher reaction kinetics and lower polarization of the Zn@h1-MXene composite anode. Figure 5 (g), at ultra-high current density (1000mA g -1 ), after 2000 cycles, the high capacity is maintained at 184.4 mAh g -1 In contrast, the capacity of the bare Zn||MnO2 full cell shows a significant decrease in the first 50 cycles and decays to less than 31.8 mAh g only after 2000 cycles. –1 .

[0138] The present invention uses COMSOL to simulate the structural stability of the electrode during the galvanizing / stripping process:

[0139] A simplified 3D model was built using the h1-MXene skeleton. Figure 6 In the figure, (a) COMSOL multiphysics simulation of the stress distribution caused by zinc plating on the entire h1-MXene scaffold. (b) Simulation of the stress distribution when two MXene nanosheets are cross-linked in the local area of ​​the h1-MXene and (c) pure MXene skeletons. (d) MD simulation of the atomic configuration of h1-MXene and pure MXene skeletons under different compressive strains. The results show that the h1-MXene skeleton exhibits excellent mechanical toughness and strength, so it is able to overcome the stress caused by volumetric strain during the cycle and maintain good structural integrity and stability. The h1-MXene composite structure can remain intact after being stretched to 150% from the initial state under stress, and fully recover to the initial state after the stress is removed. In order to further compare the structural stability of h1-MXene and pure MXene skeletons, molecular dynamics (MD) simulations were performed to further study the deformation resistance with and without the use of cross-linking agents ( Figure 6d). Due to the hydrogen bonds between MXene and PEI, the strength of the structure can be enhanced and the deformation of the structure can be limited. Compared with the h1-MXene skeleton model, the skeleton that only relies on the weak van der Waals between the MXene layers can deform freely and cause severe collapse of the structure. Therefore, the modulus of the h1-MXene skeleton under compression is much higher than that of the pure MXene skeleton. The strong hydrogen bonds between the MXene nanosheets and the polymer PEI make the skeleton have excellent mechanical properties, which can well relieve the stress caused by the volume change during the electroplating / stripping process and maintain the integrity of the skeleton structure.

[0140] The present invention uses DFT calculations, atomic force microscopy (AFM) and Kelvin probe force microscopy (KPFM) to characterize the electrodes:

[0141] Figure 7 : (a) Simulation of current density distribution in 3D h1-MXene scaffold. (b) Relative intensity distribution model of local electric field in 3D-h1 MXene electrode and (c) bare Zn electrode during Zn nucleation. (d) AFM and KPFM images of 3D h1-MXene and (e) bare Zn. (f) Laser confocal microscopy 3D topography of h1-MXene and (g) bare Zn electrodes after cycling. (h) Optimized structure of Zn adsorbed on MXene and Zn surfaces as viewed from top and side. (i) Calculation of binding energy of Zn atoms on bare Zn and MXene. From Figure 7 It can be seen from ac that the 3D h1-MXene skeleton can provide a uniformly distributed electric field on the surface through the charge redistribution effect. Therefore, Zn can be uniformly deposited in the 3D h1-MXene skeleton. In contrast, the electric field distribution of the 2D planar structure is obviously uneven, and the scattered nucleation points further develop into an inhomogeneous electric field. Figure 7 dg, h1-MXene framework has a smooth surface with small average height fluctuation (380nm) and small surface potential difference (100mV). The uniformly distributed electric field effectively ensures the uniform deposition of zinc within the h1-MXene framework. In contrast, due to the non-uniform electric field distribution, the average height of the Zn anode is 900nm and the surface potential is 160mV, which may also lead to the uncontrolled growth of dendrites and destroy the cycling stability of ZMB. In addition, due to the uneven surface, local charges accumulate at the tip and a "tip effect" occurs. This result can be further confirmed by distinguishing these analogs using laser confocal microscopy 3D topographic images. According to Figure 7 f, Large blocks, aggregates, and scattered bare surfaces on Zn foil reveal the inhomogeneous deposition of Zn. Figure 7Density functional theory (DFT) calculations were applied to verify the effect of MXene on Zn adsorption. After optimization, the geometric structure of Zn adsorbed on the MXene surface compared with bare Zn is shown in Figure 2. Figure 7 h, and then Figure 7 The corresponding binding energies are given in i. Figure 7 As shown in Fig. i, the binding energy of Zn atoms adsorbed on the MXene surface is −0.81 eV, but the energy of Zn atoms on the Zn metal surface is lower (−0.21 eV).

[0142] In summary, the h-MXene composite material of the present invention has been successfully prepared, and the aqueous zinc ion battery anode prepared therefrom shows the advantages of ultra-long life and excellent cycle stability at ultra-high current density and surface capacity.

[0143] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A h-MXene composite material, characterized in that: The raw materials for preparing the h-MXene composite material include MXene and polyethyleneimine, wherein the MXene is Ti3C2T x .

2. The h-MXene composite material according to claim 1, characterized in that The mass ratio of the MXene to polyethyleneimine is 3:(300-1000).

3. The h-MXene composite material according to claim 1, characterized in that The h-MXene composite material has a thickness of 410 to 450 μm.

4. The h-MXene composite material according to claim 1, characterized in that The h-MXene composite material has a hierarchical porous structure, an average pore diameter of 8 to 13 μm, and a pore wall thickness of 80 to 130 nm.

5. The h-MXene composite material according to claim 4, characterized in that The average channel spacing of the pore walls of the h-MXene composite material is 1.2 to 1.4 nm.

6. A method for preparing the h-MXene composite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: firstly preparing a polyethyleneimine solution and a MXene solution into a PEI-MXene hydrogel by a gel method, and then obtaining a hydrogen-bonded cross-linked MXene composite material, namely, an h-MXene composite material, by freeze drying and aging.

7. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: Step 1, ultrasonically dispersing MXene powder in distilled water to prepare a MXene dispersion; Step 2, adding the PEI solution to the MXene dispersion, stirring to obtain a mixture, vacuum filtering the mixture using a filter membrane, and washing it with distilled water several times to obtain a PEI-MXene hydrogel; Step 3, adding the collected PEI-MXene hydrogel to distilled water and vigorously stirring it using a vortex mixer to obtain a uniform PEI-MXene viscous hydrogel; Step 4: directly scrape the PEI-MXene viscous hydrogel onto the substrate, and then immediately immerse it in liquid nitrogen for ice-templating to obtain PEI-MXene foam; Step 5: freeze-dry the PEI-MXene foam; then, age the PEI-MXene foam at room temperature to prepare an h-MXene composite material.

8. The preparation method according to claim 7, characterized in that: In the step 2, the concentration of the PEI solution is (0.7-0.9) wt%.

9. The preparation method according to claim 7 or 8, characterized in that: In step 5, the freeze-drying time is 22 to 26 hours.

10. An application of h-MXene composite material, characterized in that: The h-MXene composite material according to any one of claims 1 to 5 or the h-MXene composite material prepared by the preparation method according to any one of claims 7 to 9 is used in an aqueous zinc ion battery.